Carcass evaluation procedures compared - Donald H Kropf; J L Bergkamp; J N Berroth (Kansas Agricultural Experiment Station Research Reports, 1969)
This study compared various methods of evaluating carcasses. Data from 57 barrows on feeding trials for a barrow contest at the 1968 Kansas State Fair in Hutchinson were used.The barrows went on test weighing approximately 50 pounds each and were taken off feed individually at 200- 220 pounds, held off feed over night and slaughtered at the Kansas State University Meats Laboratory. Live weight was determined immediately before slaughter and carcass weight, after a 24-hour chill. Cutting time ranged from 24 to 120 hours post-mortem.; Swine Day, Manhattan, KS, September 25, 1969
Keywords: Swine day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 151; Swine; Barrows; Carcass